Assistance needed by Freshmen-Arts and Science College students to improve their study habits - Ortiz, Cesar B. (2008)
The assistance needed to improve the study habits of freshmen college students in the School of Arts and Sciences for the first semester of school year 2005-2006 was examined. There were 45 freshmen college students randomly selected, representing 26.62%, and requested to respond to the questionnaire-checklist. Frequency counts, percentages and rank were the statistical tools used to treat the data. The research shows that the freshmen college students in the School of Arts and Sciences needed assistance to improve their study habits. These assistances were in scheduling of study time, in the study place arrangements, in preparing and working on the assignment, and preparing and taking of test. The finding point to the need to consider the nature of the learning task, the learning style of the students and the learning environment (e.g. resources and psychological climate-whether favorable or hostile) in helping the students develop and improve their study habits.
Keywords: Mindanao studies; College freshmen